Qualité physicochimique et microbiologique du lait cru de vache des races bovines locales et importées - BOUKHALFA, Khedidja (My University, 2019)
Cow's milkis a complete nutritive food, it contains most of the necessary elements for the development and maintenance of body’s functions, rich in minerals (especially calcium except of iron), proteins, vitamins and fats. This is why it promotes the lactic and pathogenic microorganisms’ developement. This work is focused on the study of the physicochemical and microbiological quality of cow's milk from different breeds including Montbeliard, Holstein, Normandy, the Fleckvieh and Guelmoise. Microbiologic alanalyzes of cow's milk showed that the results of total aerobic mesophilic flora, total coliforms and faecal coliforms do not match the recommended standards. On the other hand, the physicochemical quality of the milk is nearer or better than normal.
Keywords: Raw milk; cow; breed; local; quality; microbiological; physicochemical.